Defects of Vps15 in skeletal muscles lead to autophagic vacuolar myopathy and lysosomal disease. Issue 6 (30th April 2013) - Nemazanyy, Ivan; Blaauw, Bert; Paolini, Cecilia; Caillaud, Catherine; Protasi, Feliciano; Mueller, Amelie; Proikas‐Cezanne, Tassula; Russell, Ryan C.; Guan, Kun‐Liang; Nishino, Ichizo; Sandri, Marco; Pende, Mario; et al.
Abstract The complex of Vacuolar Protein Sorting 34 and 15 (Vps34 and Vps15) has Class III phosphatidylinositol 3‐kinase activity and putative roles in nutrient sensing, mammalian Target Of Rapamycin (mTOR) activation by amino acids, cell growth, vesicular trafficking and autophagy. Contrary to expectations, here we show that Vps15‐deficient mouse tissues are competent for LC3‐positive autophagosome formation and maintain mTOR activation. However, an impaired lysosomal function in mutant cells is traced by accumulation of adaptor protein p62, LC3 and Lamp2 positive vesicles, which can be reverted to normal levels after ectopic overexpression of Vps15. Mice lacking Vps15 in skeletal muscles, develop a severe myopathy. Distinct from the autophagy deficient Atg7−/− mutants, pathognomonic morphological hallmarks of autophagic vacuolar myopathy (AVM) are observed in Vps15−/− mutants, including elevated creatine kinase plasma levels, accumulation of autophagosomes, glycogen and sarcolemmal features within the fibres. Importantly, Vps34/Vps15 overexpression in myoblasts of Danon AVM disease patients alleviates the glycogen accumulation. Thus, the activity of the Vps34/Vps15 complex is critical in disease conditions such as AVMs, and possibly a variety of other lysosomal storage diseases.